MANAJEMEN STRATEGIK PADA PENDIDIKAN ISLAM: FONDASI TEORETIS DAN ARAH PENGEMBANGANNYA - Jasuli Jasuli; Saiful Hadi (Jurnal Manajemen Pendidikan, 2026)
Islamic education faces multidimensional challenges amid the rapid shifts of the modern world, necessitating a more planned, focused, and long-term management approach. Strategic management serves as an essential instrument to ensure that Islamic educational institutions can understand their internal potential, examine external dynamics, and determine development directions aligned with core Islamic values such as shura, amanah, and ihsan. This study explains how modern management principles including the Resource-Based View (RBV) and contingency theory can be integrated with the characteristics of Islamic education, which possesses spiritual richness, scholarly traditions, and moral excellence as strategic resources. Environmental analysis, SWOT mapping, the formulation of vision and mission, implementation, transformational leadership, and continuous evaluation become crucial elements in the strategic planning process. The discussion highlights that the success of developing Islamic education depends on the readiness of human resources, organizational adaptability, and the ability to utilize technology without disregarding Islamic identity. Ultimately, strategic management provides a framework that enables Islamic education to become a sustainable, relevant institution capable of contributing significantly to global civilization.